KETEPATAN RESELEKSI DIAGNOSA DAN KODE UTAMA BERDASARKAN ATURAN MORBIDITAS PEMBIAYAANJAMINAN KESEHATAN INA-CBGS - Linda Widyaningrum (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractOne of the indicators the quality of hospital services can be known through medical records. The quality of hospital services is based on regulation of the Minister of Health of the Republic of Indonesia Number 269 / Menkes / Per / III / 2008. According to the PERMENKES Medical Record is the file containing the notes, checks and other measures of treatment given to the patients. Qualified medical record can be seen from the accuracy in writing main diagnostic and diagnosis codes. This study aimed to analyze the relationship precision diagnostics rules and the main code of inpatient medical record document, based on the rules for financing health insurance morbidity rates of INA-CBGS at Surakarta Prof. Dr. Soeharso Orthopaedic Hospital in May 2015. The population in this study is medical records documents of inpatients of the National Health Insurance in May 2015. The number of the documents are 30 documents of 2nd class in the hospital. In this study, to collect the data, the writer uses checklist to diagnose and analyze the accuracy of the diagnosis rules and the main code and of INA-CBGs financing. The test used in this study is Chi Square. The accuracy of primary diagnosis and primary diagnosis code of Surakarta Prof. Dr. Soeharso Orthopaedic hospital is in good categories. Where the main diagnostic accuracy is 100% and primary diagnosis code is 93.3%. Health insurance financing that uses INA CBGs software can affect the accuracy of financing cost. There is a significant relationship between the accuracy of the rules of Diagnosis and Main Diagnosis Codes Document Medical Record system using financing. The results of significant value is 0.00, and p <a (0.05).Keywords: Rules of Diagnosis and Main Diagnosis Code, financing cost, INA CBGsAbstrakSalah satu indikator mutu pelayanan tersebut dapat diketahui melalui rekam medis dimana rekam medis berdasarkan peraturan Menteri Kesehatan Republik Indonesia nomor 269/MENKES/PER/III/2008 adalah berkas yang berisikan catatan, pemeriksaan, pengobatan tindakan lain yang diberikan kepada pasien. Rekam medis yang berkualitas dapat dilihat dari keakuratan menuliskan diagnose utama dan kode diagnosa. Penelitian ini bertujuan untuk menganalisa hubungan ketepatan reseleksi diagnosa dan kode utama dokumen rekam medis rawat inap berdasarkan aturan morbiditas terhadap pembiayaan jaminan kesehatan tarif INA-CBGS di Rumah Sakit Ortopedi Prof. Dr. Soeharso Surakarta Bulan Mei Tahun 2015. Populasi dalam penelitian ini adalah Dokumen rekam medis pasien rawat inap Jaminan Kesehatan Nasional pada bulan Mei 2015 kelas 2 dengan jumlah 30 dokumen dokumen. Pada penelitian ini, alat pengumpulan data yang digunakan adalah cheklist untuk menganalisa ketepatan reseleksi diagnose dan kode utama serta pembiayaan INA-CBGs. Uji yang digunakan adalah Chi Square. Keakuratan diagnosa utama dan kode diagnosa utama rumah sakit Ortopedi Prof Dr.Soeharso Surakarta masuk kategori baik. Dimana keakuratan diagnosa utama 100% dan kode diagnosa utama 93.3%. Pembiayaan Jaminan kesehatan memakai software INA CBGs dimana keakuratan kode mempengarui biaya pembiayaan. Ada hubungan yang signifikan Ketepatan Reseleksi Diagnosa Dan Kode Utama Diagnosa Dokumen Rekam Medis Dengan Pembiayaan dengan nilai signifikan 0,00, dan p < a (0,05 ).Kata Kunci : Reseleksi diagnose dan kode utama, Pembiayaan, INA-CBGS